Teachers’ Challenges on ICT Implementation Using Google Meet as Teaching Media in English Language Teaching - Cukup Wibowo; Arif Rahman; Jumadil; Hwang, Huang Yann (Journal of Language and Literature Studies, 2024)
The integration of Information and Communication Technology (ICT) in education has significantly transformed the teaching and learning process, particularly in language instruction. Among the various ICT tools, Google Meet has emerged as an innovative solution to enhance engagement and effectiveness in English language teaching, especially for young learners in junior high schools. This study aims to describe the English language teaching methods employed by English teachers to utilize Google Meet in junior high schools and identify the factors that hinder its use in the classroom. The research was conducted with English teachers at junior high schools, employing a descriptive qualitative method. Data were collected through teacher interviews and in-class observations, embracing both observational techniques and interviews. The gathered data were analyzed qualitatively through processes of reduction, data visualization, and comprehensive data analysis. To ensure the reliability of the data, researchers used triangulation methods. The findings of the study indicate that the use of Google Meet in junior high schools in Mataram is extensive, particularly with the implementation of the 2013 Curriculum and the Merdeka Curriculum. Google Meet is employed for various purposes, from managing attendance to student activation and scoring systems. To support the integration of Google Meet and reduce uncertainties in the teaching-learning process, schools have provided facilities such as Wi-Fi, projectors, sound systems, and individual Google Meet accounts for each class. Despite these advancements, the study identified several factors and conditions that limit the use of Google Meet. These include time constraints, as each teaching subject is allocated only one hour per week, and established classroom practices that may resist the adoption of new technologies.